HUBUNGAN TINGKAT KECEMASAN DAN KUALITAS TIDUR DALAM MENYELESAIKAN SKRIPSI MAHASISWA UNIVERSITAS KLABAT - Padaunan, Ellen; Wendur, Cindra Patricia (Klabat Journal of Nursing, 2026)
Sleep quality is a problem experienced by many students who are completing their thesis. One of the causes of poor sleep quality is anxiety. This study aims to determine the relationship between anxiety levels and sleep quality in completing thesis of Klabat University students. The research design used is descriptive correlation with a cross-sectional approach with convenience sampling technique Sampling on 181 respondents. The results obtained that the majority of students who are completing their thesis at Klabat University have anxiety in the mild category, namely 92 students (50.8%) and the quality of sleep in students who complete their thesis at Klabat University is mostly in the category of poor sleep quality, namely 179 students (98.9%). The results of the correlation test that has been carried out using the statistical formula, namely Spearman Rho, obtained a p-value of 0.000, which means there is a significant relationship between anxiety levels and sleep quality in completing thesis of Klabat University students with a value of r = 0.276, which means that the two variables have a weak relationship but the direction of the relationship is positive and also means that the higher the level of anxiety, the worse the quality of sleep. Recommendations that researchers can provide for future researchers who wish to conduct similar research are to be able to conduct further research on what factors can influence the anxiety of students completing their theses. Kualitas tidur adalah masalah yang dialami oleh banyak mahasiswa yang sedang menyelesaikan skripsi. Salah satu penyebab kualitas tidur buruk yaitu kecemasan. Penelitian ini bertujuan untuk mengetahui ada hubungan antara tingkat kecemasan dan kualitas tidur dalam menyelesaikan skripsi mahasiswa Universitas Klabat. Desain penelitian yang dilakukan adalah deskriptif korelasi dengan pendekatan cross-sectional dengan teknik convenience sampling Sampling pada 181 responden. Hasil yang didapat bahwa mayoritas mahasiswa yang sedang menyelesaikan skrpsi di Universitas Klabat memiliki Kecemasan yang berkategori tingkat ringan yaitu 92 mahasiswa (50,88%) dan kualitas tidur pada mahasiswa yang menyelesaikan skripsi di Universitas Klabat mayoritas berada pada kategori kualitas tidur yang buruk yaitu 179 mahasiswa (98,9%). Hasil uji korelasi yang sudah dilakukan menggunakan rumus statistik yaitu Spearman Rho didapatkan didapati p-value 0,000 yang berartinya ada hubungan yang signifikan antara tingkat kecemasan dan kualitas tidur dalam menyelesaikan skripsi mahasiswa Universitas Klabat dengan nilai r= 0,276 yang artinya kedua variabel memiliki hubungan yang lemah tapi arah hubungannya yang positif atau semakin tinggi tingkat kecemasan maka semakin buruk kualitas tidur. Rekomendasi yang dapat diberikan peneliti bagi peneliti selanjutnya yaitu melakukan penelitian lebih lanjut mengenai faktor-faktor apa saja yang bisa mempengaruhi kecemasan mahasiswa yang menyelesaikan skripsi.